Baseline Serum Prostate-specific Antigen Value Predicts the Risk of Subsequent Prostate Cancer Death—Results from the Norwegian Prostate Cancer Consortium - Bjerner, Johan; Bratt, Ola; Aas, Kirsti; Albertsen, Peter C.; Fosså, Sophie D.; Kvåle, Rune; Lilja, Hans; Müller, Christoph; Müller, Stig; Stensvold, Andreas; Thomas, Owen; Røe, Oluf D.; et al. (European urology, 2024)
Among 40- to 70-yr-old men with a “normal” prostate-specific antigen (PSA) value (below 4 ng/ml) sampled in routine medical care, the risk of dying from prostate cancer in the next two decades is associated with the PSA level. Prostate-specific antigen (PSA) levels in midlife are strongly associated with the long-term risk of lethal prostate cancer in cohorts not subject to screening. This is the first study evaluating the association between PSA levels drawn as part of routine medical care in the Norwegian population and prostate cancer incidence and mortality. The objective of the study was to determine the association between midlife PSA levels <4.0 ng/ml, drawn aspart of routine medical care, and long-term risk of prostate cancer death. The Norwegian Prostate Cancer Consortium collected >8 million PSA results from >1 million Norwegian males (more than or equal to) 40 yr of age. We studied 176 099 men (predefined age strata: 40–54 and 55–69 yr) without a prior prostate cancer diagnosis who had a nonelevated baseline PSA level (<4.0 ng/ml) between January 1,1995 and December 31, 2005. We assessed the 16-yr risk of prostate cancer mortality. We calculated the discrimination (C-index) between predefined PSA strata (<0.5, 0.5–0.9, 1.0–1.9, 2.0–2.9, and 3.0–3.9 ng/ml) and subsequent prostate cancer death. Survival curves were plotted using the Kaplan-Meier method. The median follow-up time of men who did not get prostate cancer was 17.9 yr. Overall, 84% of men had a baseline PSA level of <2.0 ng/ml and 1346 men died from prostate cancer, with 712 deaths (53%) occurring in the 16% of men with the highest baseline PSA of 2.0–3.9 ng/ml. Baseline PSA levels were associated with prostate cancer mortality (C-index 0.72 for both age groups, 40–54 and 55–69 yr). The fact that the reason for any given PSA measurement remains unknown represents a limitation. We replicated prior studies that baseline PSA at age 40–69 yr can be used to stratify a man’s risk of dying from prostate cancer within the next 15–20 yr. A prostate-specific antigen level obtained as part of routine medical care is strongly associated with a man’s risk of dying from prostate cancer in the next two decades.